A comparative study of two different doses of magnesium sulfate on pneumoperitoneum-related hemodynamics and on the recovery in patients undergoing laparoscopic gynecological surgeries: A double-blind, randomized, clinical study - Reddy Mamatha Chikkanarasimha; Rajappa Nulenur Rashmi; Venkataramaiah Vani Nitturu; Bindu Nagaraj; Nagaraja Swathi (Asian Journal of Medical Sciences, 2023)
Background: Pneumoperitoneum (PP) with carbon dioxide (CO2) induces hemodynamic response due to the release of catecholamines and vasopressin. Magnesium Sulfate (MgSo4) inhibits the release of these mediators and attenuates the hemodynamic responses to carbon dioxide PP. Aims and Objectives: This study aimed to compare two different doses of intravenous Magnesium Sulfate on attenuating PP-related hemodynamic responses. We also evaluated recovery time, the time interval between administration of the reversal agent and extubation. Materials and Methods: Seventy female patients undergoing laparoscopic surgeries were randomized into two groups. Group I received 30 mg/kg of MgSo4 and Group II received 50 mg/kg of MgSo4 intravenous infusion prior to PP, respectively. Heart rate (HR), systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP) were measured at regular intervals. The secondary outcome, Train of four ratio (TOF%), at reversal and extubation was recorded. Recovery time was noted. Results: Demographic data, HR, SBP, DBP, and MAP were comparable between groups I and II, with no clinical and statistical significance in the ‘P’ value. The mean TOF ratio (%) at reversal was lower in group II (58.47±5.40) versus group I (66.93±3.43), with a P<0.001. The mean TOF ratio (%) at extubation was lower in group II (93.70±2.39) versus group I (97.47±1.59), with a P<0.001. Recovery time in minutes was higher in group II (17.80±1.19) versus group I (13.87±0.67), with a P<0.001. Conclusion: Magnesium Sulfate 30 mg/kg and 50 mg/kg intravenous infusions prior to CO2 PP showed comparable hemodynamics in laparoscopic gynecological surgery. However, Magnesium Sulfate 50 mg/kg resulted in prolonged recovery from non-depolarizing muscle relaxants, necessitating neuromuscular monitoring for safer use.